A resource mapping framework for value co-creation in social media. (1st January 2014) - Yuan, Qian; Cai, Shuqin; Zhou, Peng
It is urgent for companies to sustain high levels of customer satisfaction in social media where customer opinions and attitudes propagate through a large population quickly. The value of customer participation has been emphasised in order to improve the information exchanging between customers and companies. Value co-creation is one of the most important ways to achieve that goal; and resources are the key issues towards value co-creation processes. To enhance competition power and improve the customer satisfaction, companies must have a deep insight of value co-creation, especially from the perspective of resources. In this paper, a resource mapping framework in social media has been given based on the value co-creation theory. The value co-creation processes have been split into three sub-processes: company resource-mapping processes, customer resource-mapping processes and encounter resource-mapping processes. Lastly, an instance has been analysed to prove the proposed framework applicability.